(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2025)
This study aims to review the effects of locus of control and time budget pressure on fraud detection. The research method used was a literature review following a quantitative approach. 100 previous studies related to the topic were obtained with relevant criteria including dependent and independent variables that are similar, with the research methods used being empirical studies, case studies, and observations, and publication years within the range of 2022 to 2024 so that the six most important previous studies were identified using a PRISMA diagram. This paper finally proposes a hypothesis about the relationship between the variables to guide future research. The results of the literature review show that: 1) locus of control has a positive impact on fraud detection; 2) time budget pressure harms fraud detection.